The Impact of Manager Likeability on Sales Performance. Issue 2 (3rd April 2019) - Nowlin, Edward L.; Walker, Doug; Anaza, Nwamaka
Abstract : This research examines whether it is important if salespeople like their manager. Little is known about the outcomes of manager likeability as perceived by the salesperson. This study introduces manager likeability and investigates its impact on salesperson performance. Drawing on interpersonal attraction and relational identification theory, we show that relational identification is the process by which manager likeability impacts performance. We demonstrate that in addition to driving performance via relational identification, manager likeability strengthens the effect identification has on salesperson performance. Additional analysis indicates that salesperson knowledge mediates the relationship between identification and performance. The study also has managerial implications for the recruiting, training, and development of sales managers.